Chemoselective Reduction of Carbonyl Compounds to Alcohols with Co-Doped Ammonia Borane - Huang1, Pengmian; Tang3, Wenjuan; Tan1, Guishan; Zeng1, Wenbin; Li1, Yuanjian; Zhang2, Qinghua; Chen2, Bo (Asian Journal of Chemistry, 2014)
Chemoselective reduction of various carbonyl compounds to alcohols with Co-doped ammonia borane was investigated in the present work. It was observed that Co-doped ammonia borane exhibited much better performance than ammonia borane. The Co-based catalysts could be reused up to four times with a slight decrease in activity. Thus, a mild and efficient method for chemoselective reduction of carbonyl compounds with Co-doped ammonia borane was established. The Co-doped ammonia borane sample was characterized by electron paramagnetic resonance. Electron paramagnetic resonance characterization revealed that Co element in a partially reduced state.